Impact of an e-cigarette tax on cigarette and e-cigarette use in a middle-income country: a study from Indonesia using a pre–post design. Issue 5 (4th May 2022) - Kowitt, Sarah D; Anshari, Dien; Orlan, Elizabeth N; Kim, KyungSu; Ranney, Leah M; Goldstein, Adam O; Byron, M Justin
Abstract : Objectives: Indonesia implemented its first e-cigarette regulation in 2018, a 57% tax on the retail price of e-cigarette liquid (e-liquid), exceeding the 40% average tax on cigarettes. Economic research suggests that this tax could unintentionally increase cigarette smoking among dual users, but this has not been examined in a low-income or middle-income country. We therefore investigated the effects of the e-liquid tax among adults in Indonesia. Design: Pre–post study. Setting: Indonesia. Participants: Adults who currently used e-cigarettes and either currently or occasionally smoked cigarettes or recently quit were recruited using Facebook and Instagram ads. Our follow-up response rate was 79%. A final sample of 1039 adults participated. Primary outcome measures: E-cigarette and cigarette use. Results: Following the e-liquid tax, participants reported paying a 4.4% higher price for e-liquid (p=0.02). Participants also reported an average 0.5-day decrease in the number of days they used e-cigarettes in the past week (p<0.001), and the proportion of daily e-cigarette users decreased (75.9% to 63.6%; p<0.001). Overall, reported use of cigarettes also declined, on average, by nine cigarettes per week. Participants who reported decreasing their e-cigarette use had higher odds of reporting increasing their cigarette use rather than reporting no change (adjusted OR: 2.99; 95% CI: 1.95 to 4.59). Further, as participants reported using e-cigarettes less frequently, they reported using cigarettes more frequently (β=−2.41, p=0.007). Conclusions: Following an e-liquid tax in Indonesia, prices of e-liquid increased slightly, e-cigarette and cigarette use declined, and people who reported decreasing their e-cigarette use reported increasing their cigarette use. To avoid encouraging cigarette use, a prudent approach would be to raise cigarette taxes concurrently with e-cigarette taxes.